2017
DOI: 10.2298/gensr1703959k
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3 polymorphism prevalence in general population of six Balkan countries

Abstract: The aim of this study was to investigate the prevalence of RR, RX and XX genotypes of rs1815739 single nucleotide polymorphism of ACTN3 gene in general population of six Balkan countries. This SNP is currently thought to give genetic predisposition for advantageous sport performance, with its R allele positively correlating with better performance in strength/power sports, and X allele being present in higher frequency in elite athletes in endurance disciplines. A total of 483 individuals (281 males and 202 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…This underrepresentation below the reference latitude populations opens a gap for further discussion within the field. This is important especially since the allelic frequencies from our study (0.68 and 0.32 for the R and X alleles, respectively) are comparable to other European (0.58 and 0.42, respectively) [47] and Balkan populations (from 0.59 and 0.41 in Serbia, 0.66 and 0.34 in Albania, to 0.79 and 0.21 in Montenegro) [46]. A factor that seems to be very specific for Kosovo and could be an important factor for genetic studies, is the fact that compared to neighboring countries-such as Albania, Macedonia, and Serbia-Kosovo has had among the lowest number of immigrants in South East Europe.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This underrepresentation below the reference latitude populations opens a gap for further discussion within the field. This is important especially since the allelic frequencies from our study (0.68 and 0.32 for the R and X alleles, respectively) are comparable to other European (0.58 and 0.42, respectively) [47] and Balkan populations (from 0.59 and 0.41 in Serbia, 0.66 and 0.34 in Albania, to 0.79 and 0.21 in Montenegro) [46]. A factor that seems to be very specific for Kosovo and could be an important factor for genetic studies, is the fact that compared to neighboring countries-such as Albania, Macedonia, and Serbia-Kosovo has had among the lowest number of immigrants in South East Europe.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, our findings are consistent with a prevalence study from six neighboring Balkan countries. Even though a relatively small number of participants (total n = 483) have been genotyped, a generally lower representation of the ACTN3 XX genotype, varying from 6.0% in North Macedonia, 6.7% in Montenegro, 12.5% in Albania, 13.1% in Croatia, 13.6% in Serbia, and 17.7% in Bosnia and Herzegovina has been confirmed [46]. From these, North Macedonia, Montenegro, Albania, and Serbia are land bordered with Kosovo.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, a data-driven modelling of the TGS may produce more accurate results because it captures features of a particular dataset that makes it different from others. In our study, through the data-driven TGS modelling we identified and described differences in genotype effects on the power and endurance traits between male and female athletes, that also were noted by other researchers [ 29 ].…”
Section: Discussionsupporting
confidence: 67%
“…They also may differ in distributions of genotypes of gene markers of physical performance. For example, gender effects with respect to ACTN3 were noted in a study of athletes of six Balkan populations [ 29 ]. The XX genotype was twice prevalent in males than females (15.7% vs. 7.4%).…”
Section: Introductionmentioning
confidence: 99%